PERTANGGUNGJAWABAN PIDANA ATAS KELALAIAN YANG MENGAKIBATKAN LUKA-LUKA DAN KEMATIAN: ANALISIS PUTUSAN NOMOR 13/PID.B/2023/PN SBY - Moch Ilyas Akbar Rizki; Maria Novita Apriyani (Universitas Labuhanbatu, 2026)
The increasing occurrence of negligence resulting in loss of life demonstrates the importance of criminal law enforcement that is capable of ensuring legal certainty and justice for both victims and perpetrators. In criminal law, negligence is understood as a form of culpability arising from a lack of caution, carelessness, or recklessness that causes harmful consequences to others. This study aims to analyze whether the element of fault was fulfilled in Decision Number 13/Pid.B/2023/PN Sby concerning the Kanjuruhan Riot Tragedy in Malang, as well as to examine the conformity of the judges’ considerations with the principles of criminal justice. This research employs a normative legal research method using statutory, case, and conceptual approaches through library research on court decisions, criminal law doctrines, and related regulations. The findings reveal that the judges’ considerations in determining the element of fault were predominantly based on trial facts and the testimonies of the defendants, thereby failing to fully accommodate the interests and sense of justice of the victims. Furthermore, this study identifies a normative gap in the application of the concept of negligence, which causes criminal liability to inadequately reflect the principles of substantive justice. Therefore, stronger parameters for assessing negligence and a more victim-oriented approach are necessary within Indonesia’s criminal justice system.Keywords: Negligence; Criminal Liability; Judicial Consideration; Substantive Justice; Kanjuruhan Tragedy